The FAMILY NURSING ASSISTANCE Mr. G WITH HYPERTENSION PROBLEMS IN Mrs. H THE GIVING OF MENTIMUN JUICE - Maldanurman Putri, Rivi; Mawarti, Indah; Sulistiawan, Andika (Program Studi Keperawatan Universitas Jambi, 2023)
Hypertension is also referred to as a non-communicable disease, because hypertension is a chronic disease that cannot be transmitted to other people. This study aims to understand and learn about nursing care in families with hypertensive clients at Garuda Bagan Pete Housing. The results of the assessment on the client found the main complaint was lack of knowledge in families with hypertension. Planning and implementation are supported by supporting facilities and means and evaluation is carried out properly. The results of the final evaluation on Mrs. H with hypertension are the family's inability to recognize family health problems. At the beginning of the study Mrs. H said she did not know about hypertension and how to treat hypertension sufferers. After being implemented for 5 meetings, namely the family was given health education about hypertension and how to treat hypertension sufferers, now Mrs. H's family is able to understand hypertension and is able to care for hypertension sufferers. And after implementing the cucumber juice intervention Mrs. H's blood pressure decreased from 160/90 mmHg to 120/90 mmHg.